Effect of two tapering methods on interleukin-6, cortisol and performance in elite male wrestler - Mehranpour, A. B.; Silalerdetkul, S.; Hasani, S. H.; Witid, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: This study examined that effect of two types of tapering on interleukin-6(IL-6), cortisol and performance in elite male wrestler.